2012
DOI: 10.1016/j.envpol.2011.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Estimating surface water concentrations of “down-the-drain” chemicals in China using a global model

Abstract: Predictions of surface water exposure to "down-the-drain" chemicals are presented which employ grid-based spatially-referenced data on average monthly runoff, population density, country-specific per capita domestic water and substance use rates and sewage treatment provision. Water and chemical load are routed through the landscape using flow directions derived from digital elevation data, accounting for in-stream chemical losses using simple first order kinetics. Although the spatial and temporal resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…It is worthy to note that the most popular drink in China is tea, which could have lower and more variable content of caffeine than coffee (Barone and Roberts, 1996). Previous studies have indicated that the economic status could influence the consumption behavior of PPCPs in different places (Bu et al, 2016;Hodges et al, 2012;Whelan et al, 2012). It was observed that caffeine and acesulfame consumption in China have good agreement with this hypothesis.…”
Section: Consumption Of Acesulfame and Caffeinesupporting
confidence: 77%
See 1 more Smart Citation
“…It is worthy to note that the most popular drink in China is tea, which could have lower and more variable content of caffeine than coffee (Barone and Roberts, 1996). Previous studies have indicated that the economic status could influence the consumption behavior of PPCPs in different places (Bu et al, 2016;Hodges et al, 2012;Whelan et al, 2012). It was observed that caffeine and acesulfame consumption in China have good agreement with this hypothesis.…”
Section: Consumption Of Acesulfame and Caffeinesupporting
confidence: 77%
“…PPCP consumption could correlate with demographic characteristics of a given population which was proposed in previous studies Whelan et al, 2012) and observed in China. It is interesting to compare the data from China with the data in Australia reported by O'Brien et al (2014) to verify whether demographic and economic characteristics affect the consumption behavior of PPCPs.…”
Section: Comparison With Australiamentioning
confidence: 90%
“…As TCS is commonly used as bactericidal additive with a maximum concentration of 0.3 % in PCPs (EC 2009), we were able to estimate the total amount of TCS consumed in the whole China. According to some studies available in literature, the usage of chemical ingredients included in the personal care products in a region corresponded well with the per capita chemical consumption (PCC) estimate (mg/cap/year) inputs and populations (Holt et al 1998;Price et al 2009;Whelan et al 2012). Based on the assumption, we distributed the TCS uniformly for the population in China.…”
Section: Emission Estimationmentioning
confidence: 90%
“…Modelling approach has provided an alternate method to solve the problem. Combining the chemical usage data, population, removal rate in WWTPs and a parameterized multimedia model describing the fate of chemicals, the chemical concentrations in the environment can be predicted, and it has been proved to be effective and accurate (Keller et al 2007;Price et al 2009Price et al , 2010aWhelan et al 2012;Zhang et al 2013). Multimedia fugacity models are well established, well documented and widely used for predicting the environmental fate of different chemicals at various scales (single river scale, regional scale and global scale) (Cao et al 2004;Mackay and Paterson 1991;Prevedouros et al 2004;Tan et al 2007;Tao et al 2003;Wang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to the GREAT-ER model, the per capita chemical consumption (PCC) of NP and NPEOs in the Wenyu River catchment needs to be estimated to simulate their emission from STPs. Given that there is no statistical information about NP and NPEOs consumption in the target area, a practical method based on the monitored STP influent concentration ranges of NP and NPEOs, total influent flows per year for each STP, and the population served by the STPs was adopted to estimate the PCCs of NP and NPEOs (Balaam et al 2010;Whelan et al 2012), which can be calculated by the following equation:…”
Section: Simulation Scenario Buildingmentioning
confidence: 99%